2023
DOI: 10.1186/s13045-023-01476-8
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1/2 study of azacitidine, venetoclax and pevonedistat in newly diagnosed secondary AML and in MDS or CMML after failure of hypomethylating agents

Abstract: Background Pevonedistat is a first-in-class, small molecular inhibitor of NEDD8-activating enzyme that has clinical activity in acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS). Preclinical data suggest synergy of pevonedistat with azacitidine and venetoclax. Methods This single-center, phase 1/2 study evaluated the combination of azacitidine, venetoclax and pevonedistat in older adults with newly diagnosed secondary AML or with MDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Novel targeted therapies incorporated into combination regimens have also been explored in the TP53 mut AML setting. Pevonedistat (PEVO)-an inhibitor of the NEDD8activating enzyme (NAE)-seems to exert antiproliferative effects on LCs, and preclinical data supports synergistic effects with AZA and VEN [55][56][57]. A phase 1b study of unfit, treatment-naïve AML patients treated with PEVO and AZA showed improved responses with an ORR of 50%, with TP53 mut patients achieving a CR and partial response (PR) rate of 80% [55].…”
Section: Targeted Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel targeted therapies incorporated into combination regimens have also been explored in the TP53 mut AML setting. Pevonedistat (PEVO)-an inhibitor of the NEDD8activating enzyme (NAE)-seems to exert antiproliferative effects on LCs, and preclinical data supports synergistic effects with AZA and VEN [55][56][57]. A phase 1b study of unfit, treatment-naïve AML patients treated with PEVO and AZA showed improved responses with an ORR of 50%, with TP53 mut patients achieving a CR and partial response (PR) rate of 80% [55].…”
Section: Targeted Treatmentsmentioning
confidence: 99%
“…Based on these results, a phase 2 study consisting of TP53 mut AML patients was conducted, but failed to show enhanced CRR rates and was prematurely terminated [56]. Intriguingly, a phase 1/2 study evaluating the efficacy of combined PEVO, AZA, and VEN in ND secondary AML reported a CR/CRi rate of 64%, but a dreadful 1-year OS of 0% in TP53 mut patients, contrary to a median OS of 18 months in TP53 wt patients [57]. Moreover, the DOR differed significantly among these patients [57].…”
Section: Targeted Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…When tested in combination with azacitidine and venetoclax in a phase 1/2 trial, the study targeted older adults recently diagnosed with secondary AML, MDS, or chronic myelomonocytic leukemia (CMML) and assessed their response rates to the specified drug combination [ 192 ]. Notably, an impressive complete remission or incomplete hematological recovery (CR/CRi) rate of 66% was observed in the AML cohort, whereas the MDS/CMML cohort demonstrated a robust overall response rate of 75%, signaling the potency of this drug combination [ 192 ]. However, the prevalence of common adverse events, such as infection and febrile neutropenia, must be considered [ 192 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, an impressive complete remission or incomplete hematological recovery (CR/CRi) rate of 66% was observed in the AML cohort, whereas the MDS/CMML cohort demonstrated a robust overall response rate of 75%, signaling the potency of this drug combination [ 192 ]. However, the prevalence of common adverse events, such as infection and febrile neutropenia, must be considered [ 192 ]. Moreover, the research findings suggest potential molecular alterations that may contribute to the development of therapeutic resistance.…”
Section: Introductionmentioning
confidence: 99%